Nomogram based on clinical characteristics and ultrasound indicators for predicting severe postpartum hemorrhage in patients with anterior placenta previa combined with previous cesarean section: a retrospective case-control study - Pin Cao; Lu Ji; Chong Qiao (BMC, 2024)
Abstract Background Placental accreta spectrum disorders (PAS) are a high-risk group for severe postpartum hemorrhage (SPPH), with the incidence of PAS increasing annually. Given that cesarean section and anterior placenta previa are the primary risk factors for PAS, therefore, our study aims to investigate the predictive value of clinical characteristics and ultrasound indicators for SPPH in patients with anterior placenta previa combined with previous cesarean section, providing a theoretical basis for early prediction of SPPH. Methods A total of 450 patients with anterior placenta previa combined with previous cesarean section were retrospectively analyzed at Shengjing Hospital affiliated with China Medical University between January 2018 and March 2022. Clinical data and ultrasound indicators were collected. Patients were categorized into SPPH (blood loss >2000mL, 182 cases) and non-SPPH (blood loss ≤ 2000mL, 268 cases) groups based on the blood loss within 24 h postpartum. The population was randomly divided into training and validation cohorts at a 7:3 ratio. LASSO and multifactorial logistic regression analyses were utilized to identify independent risk factors for SPPH. Accordingly, a nomogram prediction model was constructed, the predictive performance was assessed using receiver operating characteristic (ROC) curves, calibration curves and decision curve analysis (DCA). Results Among the 450 patients, 182 experienced SPPH (incidence rate, 40.44%). Preoperative systemic immune-inflammatory index, preoperative D-dimer level, preoperative placenta accreta spectrum ultrasound scoring system (PASUSS) score, and one-step-conservative surgery were identified as independent risk factors for SPPH in patients with anterior placenta previa combined with previous cesarean section. A nomogram was constructed based on these factors. The areas under the ROC curves for the training and validation cohorts were 0.844 (95%CI: 0.801-0.888) and 0.863 (95%CI: 0.803-0.923), respectively. Calibration curves and DCA indicated that this nomogram demonstrated good predictive accuracy. Conclusions This nomogram presents an effective and convenient prediction model for identifying SPPH in patients with anterior placenta previa combined with previous cesarean section. It can guide surgical planning and improve prognosis.